A Corpus Based Approach to the Analysis of Structures in Prepositional Phrase - Swarniti, Ni Wayan (Institut Hindu Dharma Negeri Denpasar, 2021)
The written text can not be separated from using prepositional phrase, because prepositional phrase makes a sentence complete grammatically. In this research, there was an aim that has to be achieved. Namely: to determine the structures of prepositional phrase. This research was descriptive qualitative-quantitative research. The data sources of this research were taken from phrases that have prepositional phrase in 50 articles of law. In this research, corpus linguistic was used as the method of collecting data. Corpus linguistic used an application in computer. It was AntConc3.2.4w2011. The results of the analysis were presented by using formal and informal technique. The structures of prepositional phrase found were 4 structures. They are prep + det + noun, prep + det + adj + noun, prep + noun, and prep + adj + noun. These structures were found based on some words as triggers in the software of corpus linguistics. Namely: down the, up the, around the, into the, with the, within the, through, in spite of, instead of, in the, at the and out of.